Appositions: The Future in Solarpunk and Post-Apocalyptic Fiction - Więckowska, Katarzyna (Text Matters: A Journal of Literature, Theory and Culture, 2022)
The essay discusses images of the future in solarpunk and post-apocalyptic fiction, focusing on their distinct approach to the narratives of progress, science, and individualism. The dystopian perspective of post-apocalyptic fiction is juxtaposed with the hopeful stance of solarpunk stories in order to outline the attempts to move beyond environmental pessimism and to imagine a liveable future. A reading of Cormac McCarthy’s The Road (2006), Erik M. Conway and Naomi Oreskes’s The Collapse of Western Civilization (2014), and Omar El Akkad’s American War (2017) provides an overview of early 21st-century dystopian motifs and visions, while the ideas and development of solarpunk fiction are discussed on the basis of three anthologies of short stories: Sunvault: Stories of Solarpunk and Ecospeculation (2017), Glass and Gardens: Solarpunk Summers (2018), and Multispecies Cities: Solarpunk Urban Futures (2021). The aim of the essay is to argue that apocalyptic and solarpunk fiction stand in a relationship of apposition to one another, representing dominant and emergent structures of feeling.